2005
DOI: 10.1007/s10350-004-0802-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Malone Antegrade Continence Enema in Patients With Perineal Colostomy After Rectal Resection

Abstract: After abdominoperineal resection, Malone antegrade continence enema associated to perineal colostomy provided an acceptable continence. It preserved patients' body image and resulted in a satisfying quality of life. It could become an alternative to iliac colostomy in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 41 publications
(33 reference statements)
0
29
0
6
Order By: Relevance
“…Since then, antegrade colonic washouts have become an important addition to the treatment of faecal incontinence in children and adults 21,22 . Such good results led some authors to propose the Malone procedure in association with perineal colostomy after abdominoperineal resection to provide acceptable continence and to avoid iliac colostomy 23 .…”
Section: Discussionmentioning
confidence: 98%
“…Since then, antegrade colonic washouts have become an important addition to the treatment of faecal incontinence in children and adults 21,22 . Such good results led some authors to propose the Malone procedure in association with perineal colostomy after abdominoperineal resection to provide acceptable continence and to avoid iliac colostomy 23 .…”
Section: Discussionmentioning
confidence: 98%
“…The first reports of the use of PC as a reconstructive method after APR date from the late 1960s, 10,11 and more substantial evidence of the interest in this technique has been accumulated since then by comparing its functional results and quality of life with standard procedures. [12][13][14][15]17 Patients reported that their quality of life after a PC compared favorably with patients who had received a coloanal primary anastomosis. 9 Two further studies assessed the functional results of a PC in association with the Malone procedure 12 and concluded that the results were acceptable compared with the formation of an IC.…”
Section: Discussionmentioning
confidence: 99%
“…9 Two further studies assessed the functional results of a PC in association with the Malone procedure 12 and concluded that the results were acceptable compared with the formation of an IC. 14 The functional results of patients included in the present study have been previously studied and reported 12,17 ; therefore, we considered PC as a routine treatment option for selected patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Com relação à frequência das irrigações, foi evidentemente superior à porcentagem de pacientes com CP que se auto irrigavam quatro vezes ou mais na semana em relação aos pacientes com CA e, todos os pacientes de ambos os grupos apresentaram continência satisfatória nos intervalos, com poucos episódios de diarréia (Tabela 7) e problemas relacionados a sintomas gastrintestinais (Tabela 8). Na literatura, os estudos relacionados à CP não abordaram sistematicamente o tema, um estudo reportou apenas que, 55% dos pacientes se auto irrigavam 2 a 4 vezes na semana (Velitchkov et al, 1997), enquanto outro estudo inferiu que 85% dos pacientes estavam satisfeitos com a continência, após 1 ano de cirurgia, realizando auto irrigação todos os dias (Portier et al, 2005), já um estudo mais recente com pacientes com CP com apendicecostomia para a irrigação obteve 58,3% dos pacientes com continência realizando a auto irrigação todos os dias (Penninckx et a., 2005), enquanto outro estudo somente relatou que 84,6% dos pacientes não tinham perdas fecais em 1 hora ou mais após as irrigações (Farroni et al, 2007 …”
Section: Discussionunclassified